Shipment Frequency of Exporters and Demand Uncertainty - Gabor Békés; Lionel Gérard Fontagné; Balazs Murakozy; Vincent Vicard (Center for Economic Studies and ifo Institute (CESifo), 2014)
Firms adjust to differences in market size and demand uncertainty by changing the frequency and size of their export shipments. In our inventory model, transportation costs and optimal shipment frequency are determined on the basis of demand as well as inventory and per shipments costs. Using a cross section of monthly firm-product-destination level French export data we confirm that firms adjust on both margins for market size. In a stochastic setting, firms adjust to increased uncertainty by reducing their sales and, for a given export volume, by reducing their number of shipments and increasing their shipment size.
Keywords: D40; F12; R40; 330; gravity; transport costs; frequency of trade; inventory model; firms